Women in science : 50 fearless pioneers who changed the world - Ignotofsky, Rachel, 1989- (Ten Speed Press, 2016)
A collection of artworks inspired by the lives and achievements of fifty famous women in science, technology, engineering, and mathematics, from the ancient world to the present, profiles each notable individual.